Comparative Effects of Spirulina with Iron Supplemented Sangobion Capsules among Anemic Females in Hafizabad - Aasma Batool, Muhammad Umar Zafar, Muhammad Abdullah, Hira Mumtaz, Shahida Siddique, Sobia Sattar, Aiman Rana, (Pakistan Journal of Medical & Health Sciences, 2022)
Anemia is a most common health problem in women that causes a variety of disorders in individuals, especially in females. About 80% of females suffered from anemia during pregnancy. Spirulina is a superfood that contains macronutrients and micronutrients and has 70% iron in its composition. Sangobion is an Iron Supplement active compound is Ferrous Sulphate and treated Iron-Deficiency Anemia. The current study aimed to investigate the effect of Sangobion and spirulina could increase Hemoglobin levels and Ferritin levels compared to usual supplementation in anemic females. The pre-post-test design was conducted for 8 weeks to 10 women in Go (control group) and 10 women in the intervention group G1(spirulina)and 10 women in intervention group G2 (Iron Supplement) at DHQ Hospital in Hafizabad from 1 January to March 2022. Women with age (21-35) years and Hb concentration range of 7 to 9 g/dl were included in this study. 30 Anemic Females were included in this study. The mean of Hb before the intervention was 7g/day and increased significantly to 13.5g/dl after taking spirulina for 8 weeks(p=0.001). In Contrast, women who took iron supplemented sangobion show near to significant improvement in Hb concentration.